Study on effect of different temperatures on biological characteristics of predacious mite Amblyseius longispinosus (Acari: Phytoseiidae) - Phuong Thao, Nguyen Thi; Hong Van, Nguyen Thi (Academia Journal of Biology, 2013)
Effects of temperature on biological characteristics of predacious mite Amblyseius longispinosus were investigated at 25°C, 30°C, and 35°C with a photoperiod of 16L:8D. The results showed that temperature extremtly effect the biological characteristics and life table of predacious mite Amblyseius longispinosus. When temperature increases from 25°C to 35°C, the life cycle of both males and females A.longispinosus, pre-oviposition, oviposition and post-oviposion time as well as longevity of these females are shorter. However, total egg production is highest at temperature of 30°C and lowest at temperature of 35°C. The intrinsic rates of natural (rm ) also increased as the temperature increased from 25°C to 35°C. Based on the results, the adaptation of this species to thermal temperatures was determined.